2021
DOI: 10.1186/s12885-021-08426-y
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis associated hepatocellular carcinoma on the African continent, the past, present, and future: a systematic review

Abstract: Background Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths in Africa. In Africa, the major causes of HCC include chronic infection with hepatitis B virus (HBV) and/or hepatitis C virus (HCV). Knowledge of the changes in the incidence of viral hepatitis-associated HCC over time and the factors responsible for such changes is key in informing policies for the prevention of viral hepatitis-associated HCC in Africa. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Another member of the Flaviviridae , HCV, causes hepatocellular carcinoma in a significant proportion of the chronically infected population [ 85 ]. Purification of the HCV replicase revealed an association with VCP, and p97-specific inhibitors caused abnormal localization of the NS5A protein [ 86 , 87 ].…”
Section: Viral Genome Replication and P97mentioning
confidence: 99%
“…Another member of the Flaviviridae , HCV, causes hepatocellular carcinoma in a significant proportion of the chronically infected population [ 85 ]. Purification of the HCV replicase revealed an association with VCP, and p97-specific inhibitors caused abnormal localization of the NS5A protein [ 86 , 87 ].…”
Section: Viral Genome Replication and P97mentioning
confidence: 99%
“…The HBV infection would be responsible of half of all cases of HCC. 3 The statistics show that there are 350 million HBV chronic carriers from a total of 2 billion infected people. Sub Saharan Africa and East Asia are ranked among the highest prevalence zones where 10% of the population are chronic carriers.…”
Section: Introductionmentioning
confidence: 99%
“…They noticed a steady increase of 1.52% each decade, but this was not statistically significant. They suggested that the incidence could be higher with statistically significant if a better screening and diagnostic capacity for HCC is done in African countries (29). The lack of basic epidemiological data regarding the actual situation of HCC is a massive constraint against better assessment and evaluation, in our opinion.…”
Section: Discussionmentioning
confidence: 98%